ANALISIS RASIO LIKUIDITAS DAN RASIO PROFITABILITAS SEBAGAI ALAT UNTUK MENGUKUR KINERJA KEUANGAN PADA PT GUDANG GARAM Tbk (PERIODE TAHUN 2014-2023) - Nabila Khairunnisa; Sri Mardiana (Journal of Research and Publication Innovation, 2025)
This research aims to determine the financial performance of PT Gudang Garam Tbk for the 2014-2023 period, when viewed from the Liquidity Ratio and Profitability Ratio. In this research, researchers used associative quantitative research. The population and sample of this research are the financial reports of PT Gudang Garam Tbk for the period 2014-2023 which consist of Tbk's balance sheet and profit and loss report for 10 years. Data collection techniques were carried out using documentation techniques and literature studies. The results of this research show that the financial performance in terms of the Liquidity Ratio of PT Gudang Garam Tbk which is measured by the Current ratio from 2014-2023 on average is 201%, which can be declared